PUBLIC SERVICE FIVE-FINGER HYPNOSIS THERAPY IN FACING ANXIETY IN ELEMENTARY SCHOOL CHILDREN AT SDN 43 PEKANBARU - Rahmaniza, Rahmaniza; Nadia, Fatma; Mianna, Rika (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Corona Virus Disease 2019 (Covid-19) is a pandemic because all countries in the world have been affected by this outbreak so it has an impact on various aspects of life such as the economy, health, and education. Five-finger hypnosis is a form of self-hypnosis that can cause a high relaxation effect that will reduce tension and anxiety in a person's mind so that it affects the production of hormones that can spur the onset of anxiety. Schoolchildren have never had Five-finger Hypnosis Therapy at school, Covid 19 conditions schoolchildren learn online and only focus on subjects. The new normal condition of learning time alternately some enter the morning and some enter the afternoon, if not given Five finger Hypnosis Therapy then the child is less able to face anxiety. The main problem faced by partners is SDN 43 Pekanbaru, namely that its students have never been given five-finger hypnosis therapy, so five-finger hypnosis therapy will be carried out in the face of anxiety in school children. Before and after the activity, an assessment of the initial and final abilities of the participants will be carried out, so that from this activity a measurable increase in knowledge will be obtained. The majority of respondents with moderate anxiety were 33 respondents (57.9 %). the majority of respondents with moderate anxiety were 31 respondents (54.4 %). there is an influence of PKM Five Finger Hypnosis Therapy in Dealing with Anxiety in Elementary School Children at SD Negeri 43 Pekanbaru on pre-test and post-test.